Relationship between Self Efficacy, Work-Life Balance to Job Satisfaction: A Proposed Employee Engagement Mediation Model - Andriani, Della; Hermawan, Iwan; Rini, Nur (Pusat Riset dan Inovasi Nasional, 2023)
The concept of employee engagement (EE) is one of the benchmarks in determining employee job satisfaction (JS) which is currently trending and continues to grow in the business world. Engagement is not just a matter of feeling but must be combined with action. Companies that implement employee engagement (EE) will increase productivity which leads to company progress. However, it is not easy for a company to implement employee engagement (EE). The concept of employee engagement (EE) is offered to bridge the insignificance gap. The direction of this research aims to determine the effect of self efficacy (SE) and work life balance (WLB) mediated by employee engagement (EE). Sampling in this study involved 208 employees. The results of the questionnaires distributed obtained a total of 203 respondents with data that could be processed as many as 192. The sample adequacy in this study was 105 so that it was declared fulfilled. Sampling was done with saturated sample technique. The analytical tool in this study uses a Structural Equation Model (SEM) which is processed with AMOS software. The results of the analysis show that self efficacy (SE) and work life balance (WLB) indirectly affect job satisfaction (JS). The contribution of research to fill the body of knowledge through attribution theory by raising the variables of SE, WLB, EE, to JS while managerial implications by building employee training and development, holding gathering activities, and providing adequate facilities for employees. Keywords: self efficacy, work life balance, employee engagement, job satisfaction